Review of the sponge genus Penares (Demospongiae, Tetractinellida, Astrophorina) in the New Zealand EEZ, with descriptions of new species - Sim-Smith, Carina; Kelly, Michelle (Zootaxa, 2019)
The genus Penares Gray 1867 (Tetractinellida Marshall; Astrophorina Sollas; Geodiidae Gray) is reviewed from new and existing New Zealand collections, with 75 specimens examined and registered. The only species known from New Zealand prior to this study, P. tylotaster Dendy 1924, is re-examined and re-described from the holotype, using new scanning electron microscope images. Nine new species are described from New Zealand’s Exclusive Economic Zone: P. mollis sp. nov., P. aureus sp. nov., P. vermiculatus sp. nov., P. kermadecensis sp. nov., P. turmericolor, sp. nov., P. deformis sp. nov., P. okokewae sp. nov., P. orbis sp. nov., and P. astronavis sp. nov. A specimen of P. schulzei (Dendy 1905), first described from Sri Lanka and subsequently recorded from New Caledonia, was also found in New Zealand, extending the range of this species. This study brings the total New Zealand Penares fauna to 11 species, making a significant contribution to the now, global total of 39 species. All previously described Penares species are reviewed based on their published descriptions, and species names have been corrected to their masculine form. Based on the published description of P. obtusus Lendenfeld 1907, it is recommended that this species be reassigned to the genus Stelletta Schmidt 1862.